Adaptive Sliding Mode Control Design for a Class of Nonlinear Systems with Unknown Dead Zone of Unknown Bounds Design - Jasim, Ibrahim Fahad; Jasim, Najah Fahad (Iraqi Journal for Electrical and Electronic Engineering, 2010)
The control problem for a class of a nonlinear systems that contain the coupling of unmeasured states and unknown parameters is addressed. The system actuation is assumed to suffer from unknown dead zone nonlinearity. The parameters bounds of the unknown dead zone to be considered are unknown. Adaptive sliding mode controller, unmeasured states observer, and unknown parameters estimators are suggested such that global stability is achieved. Simulation for a single link mechanical system with unknown dead zone and friction torque is implemented for proving the efficacy of the suggested scheme.